Socio‐economic predictors of time to care home admission in people living with dementia in Wales: A routine data linkage study - Joseph Hollinghurst (International Journal of Geriatric Psychiatry, 2021)
ObjectivesLimited research has shown that people with dementia (PwD) from lower socio-economic backgrounds can face difficulties in accessing the right care at the right time. This study examined whether socio-economic status (SES) and rural versus urban living location are associated with the time between diagnosis and care home admission in PwD living in Wales, UK.